Paroxysmal Nocturnal hemoglobinuria - Khan, Muhammad Ali; Khan, Parwez; Din, Zia ud; Khan, Jehanzeb (Journal of Postgraduate Medical Institute, 2011)
Paroxysmal Nocturnal Hemoglobinuria is a rare hemolytic anemia, affecting young adults. We report a case and present the clinical and laboratory data of this peculiar disorder. Its complications and treatment are also discussed.